Rhizospheric and phylloplane bacteria from Capsicum annuum: Uncovering candidates for biocontrol of Ralstonia solanacearum (Scientia Agropecuaria, 2025)
Ralstonia solanacearum, the causative agent of bacterial wilt, is a major plant pathogen affecting many economically significant crops, including pepper (Capsicum annuum). This pathogen causes severe yield losses due to the limited effectiveness of current control measures. This study aimed to evaluate potential biocontrol agents for managing Ralstonia solanacearum by isolating and testing microorganisms from the rhizosphere and phylloplane of pepper plants. A total of 32 bacterial isolates were screened, and four strains showed the most pronounced antagonistic activity in vitro, producing inhibition zones ranging from 4.0 to 6.12 cm. The most effective isolates included three rhizospheric strains identified as Bacillus sp., Serratia sp., and Pseudomonas sp., and one phylloplane strain identified as Pseudomonas aeruginosa. These microorganisms effectively suppressed Ralstonia solanacearum growth under laboratory conditions and show strong potential as biocontrol agents for bacterial wilt in pepper crops.
Keywords: Ralstonia solanacearum; biocontrol; Pseudomonas; halo; inhibition